2018
DOI: 10.31538/alsuna.v1i2.87
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Reading Habit and Students’ Reading Comprehension Achievements

Abstract: This research concerned with the correlation between reading habit and students’ reading comprehension acheivements. The method used was correlational design. The population and samples were 37 Students. Questionnaire and documentation were used to collect the data. The researchers used Pearson Product Moment Correlation to analyze the data. The results showed that r-obtained was 0.353 compared to r-value interpretation of 0.200 to 0.400 which means there was a low correlation. Yet, r-table of 37 students was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 2 publications
4
5
0
1
Order By: Relevance
“…Likewise, reading habits contribute significantly to ESL learners' reading achievement. These findings concur with previous investigations of the association between reading habits and reading comprehension (Balan et al, 2019;Sulaiman & Harpiansi, 2018;Najnawati, 2019;Ribqotul, 2020). Similarly, these findings are consistent with Information Transfer theory, particularly Gough's reading model, which presumes that reading represents a method of information transfer, and in the process of information transfer, reading habits play a critical role (Gough, 1972).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Likewise, reading habits contribute significantly to ESL learners' reading achievement. These findings concur with previous investigations of the association between reading habits and reading comprehension (Balan et al, 2019;Sulaiman & Harpiansi, 2018;Najnawati, 2019;Ribqotul, 2020). Similarly, these findings are consistent with Information Transfer theory, particularly Gough's reading model, which presumes that reading represents a method of information transfer, and in the process of information transfer, reading habits play a critical role (Gough, 1972).…”
Section: Discussionsupporting
confidence: 93%
“…A recent study also revealed a significant association between reading habits and composition writing amongst ESL learners (Mwangi & Bwire, 2020). Likewise, reading habits are important determinants of success in reading comprehension (Balan et al, 2019;Sulaiman & Harpiansi, 2018;Muawanah, 2016;Najnawati, 2019;Ribqotul, 2020). Through extensive reading of academic and non-academic materials, ESL learners tend to develop critical thinking skills, vocabulary mastery, language confidence, and comprehension, which eventually leads to high academic achievements (Balan et al, 2019;Muawanah, 2016;Bendriss & Golkowska, 2011;Ribqotul, 2020).…”
Section: Reading Habits and Academic Performance In The Esl Contextmentioning
confidence: 99%
“…Likewise, reading habits contribute significantly to ESL learners' reading achievement. These findings concur with previous investigations of the association between reading habits and reading comprehension (Balan et al, 2019;Sulaiman & Harpiansi, 2018;Najnawati, 2019;Ribqotul, 2020). Similarly, these findings are consistent with Information Transfer theory, particularly Gough's reading model, which presumes that reading represents a method of information transfer, and in the process of information transfer, reading habits play a critical role (Gough, 1972).…”
Section: Discussionsupporting
confidence: 93%
“…A recent study also revealed a significant association between reading habits and composition writing amongst ESL learners (Mwangi & Bwire, 2020). Likewise, reading habits are important determinants of success in reading comprehension (Balan et al, 2019;Sulaiman & Harpiansi, 2018;Muawanah, 2016;Najnawati, 2019;Ribqotul, 2020). Through extensive reading of academic and non-academic materials, ESL learners tend to develop critical thinking skills, vocabulary mastery, language confidence, and comprehension, which eventually leads to high academic achievements (Balan et al, 2019;Muawanah, 2016;Bendriss & Golkowska, 2011;Ribqotul, 2020).…”
Section: Reading Habits and Academic Performance In The Esl Contextmentioning
confidence: 99%